2018
DOI: 10.1108/jcom-12-2016-0099
|View full text |Cite
|
Sign up to set email alerts
|

Improving risk communication and public participation through mutual understanding

Abstract: Purpose Risk communication and public participation are often hampered by conflicts and mistrust between involved actors. The present paper argues that these problems can be addressed through better mutual understanding. This argument is founded on the conceptualisation of risk communication as a social interaction, which is based on mutual understanding. The purpose of this paper is to illustrate the relationship between conflict, mistrust and mutual misunderstanding through a case study. Design/methodology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…(1) may increase the risk of citizens sticking to their positions and of leaving conflict unclarified. ( 2) harbors the risk of actors' false consensus (Umansky and Fuhrberg, 2018), that is, mutual agreement on the stakes based on actors' inaccurate understanding of these stakes, as the categories and their implied meaning for citizens' stakes had no consequentiality during the interaction. False consensus can lead to actors' joint agreement on an action program that, in retrospect, turns out not to meet citizens' legitimate interests, hence questioning the validity of the SD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(1) may increase the risk of citizens sticking to their positions and of leaving conflict unclarified. ( 2) harbors the risk of actors' false consensus (Umansky and Fuhrberg, 2018), that is, mutual agreement on the stakes based on actors' inaccurate understanding of these stakes, as the categories and their implied meaning for citizens' stakes had no consequentiality during the interaction. False consensus can lead to actors' joint agreement on an action program that, in retrospect, turns out not to meet citizens' legitimate interests, hence questioning the validity of the SD.…”
Section: Discussionmentioning
confidence: 99%
“…Biased perceptions can lead to mutual distrust and conflicts. A need exists to establish mutual understanding and common ground (Umansky and Fuhrberg, 2018). JCOM 28,2 However, organizers' perception that controversies and conflicts equate to risk guides them in SD planning and implementation: Lane (2018) and Russmann and Lane (2020) show that organizers perceive opposing opinions as risks, prioritizing organizational goals, controlling interaction and avoiding controversies and interaction with stakeholders with dissenting views, and striving to accomplish predefined outcomes.…”
Section: Risk In Stakeholder Dialogmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the relative importance of disaster information on risk reduction, stakeholders at global, regional and local levels have doubled investment to intensify awareness (Paton et al, 2001;Ballantyne, 2000). Empirical evidence has shown that information sharing and response to enquiries between the senders and receivers reduce message ambiguity and improves message clarity (Bolkan et al, 2016;Broeckelman-Post et al, 2016;Sidelinger and McCroskey, 1997;Tang et al, 2015;Umansky and Fuhrberg, 2018).…”
Section: Model and Hypotheses Developmentmentioning
confidence: 99%
“…Consequently, there is an emerging consensus on the need to understand the role of different aspects of risk communication in influencing disaster preparedness (Sutton et al, 2014). Given the global susceptibility to increasing disaster risks in light of rising climate change, especially in developing regions (Intergovernmental Panel on Climate Change, 2018; Okyere et al, 2019), it is of fundamental importance to move beyond merely providing adequate information to Mediating effects of message clarity ensuring clear and comprehensible information delivered through trustworthy sources for public to act on preparing for disasters (Umansky and Fuhrberg, 2018). In pursuance of this, this paper examines the relationship between information sufficiency, message clarity, source credibility and intentions to prepare.…”
Section: Introductionmentioning
confidence: 99%